Uranium hydrogeochemical and stream sediment reconnaissance of the Skagway NTMS quadrangle, Alaska (Bendix Field Engineering Corporation, 1981)
Results of a hydrogeochemical and stream sediment reconnaissance of the Skagway NTMS quadrangle, Alaska are presented. In addition to this abbreviated data release, more complete data are available to the public in machine-readable form. In this data release are location data, field analyses, and laboratory analyses of several different sample media. For the sake of brevity, many field site observations have not been included in this volume. These data are, however, available on the magnetic tape. Appendices A and B describe the sample media and summarize the analytical results for each medium. The data were subsetted by one of the Los Alamos National laboratory (LANL) sorting programs into groups of stream sediment and lake sediment samples. For each group which contains a sufficient number of observations, statistical tables, tables of raw data, and 1:1000000 scale maps of pertinent elements have been included in this report.